Removing Intellectual Property Barrier: A Solution To Renewable Energy Technology Transfer - Shelly Kurniawan (IHSA Institute, 2022)
Renewable energy currently becomes one of the global issues. Not all developing countries are capable of inventing or making renewable energy technology. In this regard, the intellectual property serves as a hindrance. The present study aims to further identify hindrances in recreating renewable energy technological invention, as it is protected by intellectual property. This normative legal study reviews literature and other sources relevant to technology transfer, intellectual property, and renewable energy. It concludes that reengineering, as a developmental effort, is difficult to be done within the context of technology transfer. It is possible to perform renewable energy invention reengineering by applying specific stipulation that does not harm the inventor’s moral and economic rights